Changes in physico-chemical characteristics of bitter gourd (Momordica charantia) fruits harvested at different stages in controlled environments - SINGH, AWANI KUMAR; BEHERA, TUSAR KANTI; RUDRA, SHALINI GAUR; AHAMAD, SAJEEL; KUMAR, DEVESH; SINGH, ARJUN; FARUK, MOHD (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2021–2022 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate the impact of different harvesting stages on quality and storage life of two bitter gourd (Momordica charantia L.) varieties (Pusa Rasdar and S-32) grown under polyhouse conditions. The experiment was laid out in a factorial randomized complete block design (FRCBD). Results showed that S-32 achieved the longest fruit length (19.87 cm) at 24 days after pollination (DAP), while Pusa Rasdar had the largest fruit diameter (6.23 cm) and highest fruit weight (153.22 g). Pusa Rasdar also recorded the highest fruit juice content (61.65%) at 24 DAP. However, S-32 exhibited greater chlorophyll levels, with the highest chlorophyll-a (10.12 µg/g FW), chlorophyll-b (4.56 µg/g FW), and total chlorophyll content (14.68 µg/g FW) at 16 DAP. The maximum total carotenoids content was recorded in S-32 (3.63 µg/g FW) at 24 days after pollination compared to Pusa Rasdar (2.36 µg/g FW). In S-32 lines, the highest saponin content (0.95 mg/g DW) and maximum charantin levels (0.39 mg/g DW) were observed at 16 DAP, highlighting their superior biochemical composition at this stage. Biochemical compounds peaked at 16 DAP and declined thereafter, indicating early harvest favours nutritional quality, while later stages improve physical traits. The findings revealed that S-32 lines exhibited better retention of quality attributes, such as saponin and charantin, than the Pusa Rasdar variety. Notably, S-32 lines superior over Pusa Rasdar in terms of physical and biochemical parameters full fill the commercial and nutritional needs of consumers.